1998
DOI: 10.1002/(sici)1096-9861(19980112)390:2<167::aid-cne1>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Organization in the auditory sector of the cat's thalamic reticular nucleus

Abstract: This study describes the organization of cells in the thalamic reticular nucleus (TRN) that project to the auditory part of the cat's dorsal thalamus. Injections of wheat germ agglutinin conjugated to horseradish peroxidase (WGA-HRP) and fluorescent dyes were made into the medial geniculate complex (MG). The resultant retrograde labelling in the TRN was analyzed. Injections of WGA-HRP into the ventral (MGv), dorsal (MGd), or medial (MGm) nuclei of the MG label zones of cells that are restricted to a caudoventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…The TRN neurons extend dendrites within the thin reticular sheet, which enable them to receive projections from a wide cortical region, and project to widespread areas in the ventroposterior nucleus of the thalamus (Liu et al, 1995). These, together with the results of other studies, lead to the reasonable conclusion that the control of the thalamus via the TRN is widespread (Jones, 1975(Jones, , 1985Ohara et al, 1980;Yen et al, 1985;Liu et al, 1995;Bourassa et al, 1995;Cox et al, 1997;Crabtree, 1998;Crabtree and Isaac, 2002).…”
Section: Slow Oscillationmentioning
confidence: 81%
“…The TRN neurons extend dendrites within the thin reticular sheet, which enable them to receive projections from a wide cortical region, and project to widespread areas in the ventroposterior nucleus of the thalamus (Liu et al, 1995). These, together with the results of other studies, lead to the reasonable conclusion that the control of the thalamus via the TRN is widespread (Jones, 1975(Jones, , 1985Ohara et al, 1980;Yen et al, 1985;Liu et al, 1995;Bourassa et al, 1995;Cox et al, 1997;Crabtree, 1998;Crabtree and Isaac, 2002).…”
Section: Slow Oscillationmentioning
confidence: 81%
“…Metabotropic receptors, however, such as the GABA B receptor with its potassium conductance have a longer time constant and are plausible candidates in the MGB (Tennigkeit et al, 1998(Tennigkeit et al, , 1999Schwarz et al, 2000). Because GABAergic interneurons are missing in the rodent vMGB (Winer and Larue, 1996;Arcelli et al, 1997), the cortex could act via the GABAergic projection neurons from the TRN (Crabtree, 1998;Winer et al, 1999) as demonstrated recently . The axonal projection pattern of TRN cells as described in the rat (Kimura et al, 2007) is well suited to Figure 11 A (bottom).…”
Section: Roving Oddball Paradigm: Tradeoff Between Frequency Range Anmentioning
confidence: 94%
“…In rats, cats, rabbits, and primates, cortical and thalamic afferents in TRN are topographically organized (Crabtree and Killackey, 1989;Cicirata et al, 1990;Conley and Diamond, 1990;Cornwall et al, 1990;Crabtree, 1992aCrabtree, ,b, 1996Crabtree, , 1998Crabtree, , 1999Lozsadi, 1994Lozsadi, , 1995Ilinsky et al, 1999). Along the rostrocaudal axis, centroposterior loci in TRN are respectively linked with the somatosensory, visual, and auditory cortices and their associated thalamic nuclei.…”
Section: Topography Of Cortical Projections In Trn: the Prefrontal Sementioning
confidence: 99%